1998
DOI: 10.1021/bi972927q
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Intercalating Alkaloid Cryptolepine Interferes with Topoisomerase II and Inhibits Primarily DNA Synthesis in B16 Melanoma Cells

Abstract: Cryptolepine hydrochloride is an indoloquinoline alkaloid isolated from the roots of Cryptolepis sanguinolenta. It is characterized by a multiplicity of host-mediated biological activities, including antibacterial, antiviral, and antimalarial properties. To date, the molecular basis for its diverse biological effects remains largely uncertain. Several lines of evidence strongly suggest that DNA might correspond to its principal cellular target. Consequently, we studied the strength and mode of binding to DNA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
138
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(148 citation statements)
references
References 40 publications
(50 reference statements)
7
138
0
1
Order By: Relevance
“…Extracts of the roots are used in decoction to treat fevers due to malaria and stomach disorders [4]. Cryptolepine presents a large spectrum of biological properties, including hypotensive and antipyretic, antimuscarinic, antibacterial and antiinflammatory effects [5]. It also possesses potent activity in vitro against Plasmodium falciparum, which is one of the main parasite species responsible for malaria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracts of the roots are used in decoction to treat fevers due to malaria and stomach disorders [4]. Cryptolepine presents a large spectrum of biological properties, including hypotensive and antipyretic, antimuscarinic, antibacterial and antiinflammatory effects [5]. It also possesses potent activity in vitro against Plasmodium falciparum, which is one of the main parasite species responsible for malaria.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of this antimalarial product remains unclear; at least two independent effects may together lead to a potent activity. First, it behaves like a DNA intercalator with a preference for GC-rich sequences [5]. Second, it may act like chloroquin by inhibiting the detoxification of haeme in red blood cells [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaloids are a diverse group of secondary metabolites found to have antimicrobial activity by inhibiting DNA topoisomerase [22]. Alkaloid constituents in flower showed that the chloroform extract had higher amounts (0.72±0.03) atropine/g of the extract followed by (0.66±0.02) atropine/g of the ethyl acetate extract.…”
Section: Quantitative Estimation Of Phenol and Alkaloid Compoundsmentioning
confidence: 99%
“…For alkaloids, they were intensively reported to possess dignified antimicrobial due to their potency for DNA intercalation and/or topoisomerase inhibition [13]. The functional antimicrobial activity of flavonoids may be because of their capability of complexing with soluble extracellular proteins and with the microbial cell walls [14].…”
mentioning
confidence: 99%